Faktor-faktor yang memengaruhi seksualitas pada perempuan dengan HIV: Telaah sistematis - Sari, Levi Anggriani Purnama; Afiyanti, Yati; Susanti, Suryane Sulistiana; Rachmawati, Imami Nur (Holistik Jurnal Kesehatan, 2025)
Background: Sexuality is part of basic human needs that has not received attention and is considered less important, both in social services and in care. There are several factors that influence sexuality in women with HIV, such as the interaction of biological, psychological, social, economic, political, cultural, legal, historical, religious and spiritual factors. Purpose: To identify and analyze various factors that influence sexuality in women with HIV. Method: A systematic review of cross-sectional and cohort studies was conducted in September 2024 using 6 databases, namely Clinicalkey, Clinicalkey Nursing, Scopus, ScienceDirect, SpringerLink, Proquest, and Taylor & Francis. The keywords used were "WLHIV or (PLHIV) and sexuality or (sex) and related factors or (influenced factors) or (biological factors) or (psychological factors) or (social factors) or (cultural factors) or (economic factors)" or "HIV women and sexuality or (sex) and related factors". Results: Based on 13 articles that have been reviewed, several factors were found that influence sexuality in women with HIV, including biological, psychological, socio-political, and spiritual factors as well as sexual health service factors in women with HIV. Conclusion: Sexuality is influenced by the interaction of various factors, including biological, psychological, socio-political, and spiritual factors as well as sexual health service factors in women with HIV. Suggestion: Further research can examine risk factors for sexual health problems in women with HIV partner-based interventions.   Keywords: Human Immunodeficiency Virus (HIV); Sexuality; Women.   Pendahuluan: Seksualitas merupakan bagian kebutuhan dasar manusia yang belum menjadi perhatian dan dianggap kurang penting, baik dalam pelayanan sosial maupun dalam perawatan. Terdapat beberapa faktor yang memengaruhi seksualitas pada perempuan dengan HIV, seperti interaksi faktor biologis, psikologis, sosial, ekonomi, politik, budaya, hukum, sejarah, agama dan spiritual. Tujuan: Untuk mengidentifikasi dan menganalisis berbagai faktor yang memengaruhi seksualitas pada perempuan dengan HIV. Metode: Penelitian telaah sistematis terhadap studi cross sectional dan Kohort, dilakukan pada bulan September 2024 menggunakan 6 database meliputi Clinicalkey, Clinicalkey Nursing, Scopus, ScienceDirect,  SpringerLink, Proquest, dan Taylor & Francis. Kata kunci yang digunakan yaitu “WLHIV or (PLHIV) and sexuality or (sex) and associated factors or (influenced factors) or (biological factors) or (psychological factors) or (social factors) or (cultural factors) or (economical factors)” atau “women HIV and sexuality or (sex) and associated factors”. Hasil: Berdasarkan 13 artikel yang telah ditelaah, didapatkan bahwa terdapat beberapa faktor yang memengaruhi seksualitas pada perempuan dengan HIV, diantaranya adalah faktor biologis, psikologis, sosial politik dan spiritual serta faktor pelayanan kesehatan seksual terhadap perempuan dengan HIV. Simpulan: Seksualitas dipengaruhi oleh interaksi berbagai faktor diantaranya yaitu faktor biologis, psikologis, sosial politik dan spiritual serta faktor pelayanan kesehatan seksual terhadap perempuan dengan HIV. Saran:. Penelitian selanjutnya dapat meneliti mengenai faktor risiko masalah kesehatan seksual pada perempuan HIV intervensi berbasis pasangan.   Kata Kunci: Human Immunodeficiency Virus (HIV); Perempuan; Seksualitas.